Effect of diets with polychaetes on the reproductive performance of female shrimp Cryphiops caementarius, during successive spawning - Zavala-Zavaleta, Iliana (2022)
The aim of this study was to evaluate the effect of diets containing polychaetes on the reproductive performance of female Cryphiops caementarius shrimp during successive spawning. The shrimp came from the Pativilca river (Peru). The maturation system consisted of nine fiberglass tanks (100 L), each with six individual culture containers. The treatments were: basal diet, diet based on fresh polychaetes and basal diet supplemented with polychaete meal. The polychaetes (Neanthes succinea, Halosydna brevisetosa and Nereis pelagica) came from a mollusk culture system. The experiment lasted 90 days. Females fed fresh polychaetes and the basal diet supplemented with polychaete meal matured in 17.16 and 19.61 days, respectively (p<0.05) and maintained four successive spawning. In contrast, with the basal diet they matured in 24.45 days and there were only three successive spawning. Fecundity was high (p<0.05) in the first spawning of females fed polychaetes (4007 and 3472 eggs) and low with the basal diet (2165 eggs) but decreased in successive spawning. Neither diet affected the volume of newly spawned eggs, but palmitic, stearic, and oleic acid content were high in the polychaete diets. Reproductive effort and reproductive performance were high in the first spawning of polychaete-fed females but decreased in successive spawning.